Trucking regulation : lessons from Europe - Moore, Thomas Gale. (Washington : American Enterprise Institute for Public Policy Research, 1976)
The book covers Regulation of trucking in Great Britain, Regulation in West Germany, Regulation in Belgium, Regulation in the Netherlands, regulation in Sweden, Comparisons, and Lessons for the United States.
Includes bibliographical references.
rpm 22/01/2019
Loans
Keywords: Transportation, Automotive - regulation and law; Europe